DIAGNÓSTICO HIDROGEOLÓGICO DA R.M.S.P. USO E PROTEÇÃO - REBOUÇAS, ALDO DA CUNHA; RICCOMINI, CLÁUDIO; ELLERT, NELSON; DUARTE, URIEL; MELLITO, KÁTIA MARIA; SENF, LÍDIA ANDREA; DE SOUZA, JOÃO CARLOS SIMANKE (Águas Subterrâneas, 1994)
RESUMO NÃO DISPONÍVEL